Effects of vitamin D supplementation on inflammatory response in patients with cancer and precancerous lesions: systematic review and meta-analysis of randomized trials - Gwenzi, Tafirenyika; Zhu, Anna; Schrotz-King, Petra; Schöttker, Ben; Hoffmeister, Michael; Brenner, Hermann (Clinical nutrition, 2023)
Background & aims - Inflammation plays a key role in tumor development and progression. Vitamin D has potential tumor suppressing effects through modulation of inflammatory processes. The aim of this systematic review and meta-analysis of randomized controlled trials (RCTs) was to summarize and evaluate the effects of vitamin D3 supplementation (VID3S) on serum inflammatory biomarkers among patients with cancer or pre-cancerous lesions. - Methods - We searched PubMed, Web of Science and Cochrane databases until November 2022. The effects of VID3S were estimated from pooled standardized mean differences (SMDs) with their 95% confidence intervals (CIs) for inflammatory biomarker follow-up levels between intervention and control groups. - Results - Meta-analysis of eight RCTs (total of 592 patients with cancer or pre-cancerous conditions) showed that VID3S significantly lowered levels of serum tumor necrosis factor (TNF)-α (SMD [95%CI]: −1.65 [−3.07; −0.24]). VID3S also resulted in statistically non-significantly lower serum levels of interleukin (IL)-6 (SMD [95%CI]: −0.83, [−1.78; 0.13]) and C-reactive protein (CRP) (SMD [95%CI]: −0.09, [−0.35; 0.16]), whereas IL-10 levels were unaltered (SMD [95%CI]: −0.00, [−0.50; 0.49]). - Conclusion - Our study shows evidence of a significant reduction of TNF-α levels by VID3S for patients with cancer or precancerous lesions. Patients with cancer or precancerous lesions may benefit from personalized VID3S in suppressing tumour-promoting inflammatory response. - Prospero registration number - CRD42022295694.
Online verfügbar: 17. Mai 2023, Artikelversion: 14. Juni 2023
Gesehen am 01.08.2023